Barcelona runner: turismo, ciudad y cuerpos posthumanos - Herrera Altamirano, Elisa (Eracle. Journal of Sport and Social Sciences, 2019)
In this article I present acritical reading of urban running in Barcelona based on mobile ethnographic fieldwork carried out during 2015-2018. Through the analysis of specific tourist expressions of running narrated and lived by recreational runners and political actors. I explain how runners ́ bodies relate and perform constantly with the urban context to become more-than-human materialities. The exploration of touristic everyday life running practices, the design of the marathon route in Barcelona and the running tours in the city reveal how runners ́ embodied experiences of pain and pleasure, feelings of belonging, solidarity, celebration and imagination of the future emerge in continuity with the urban context. Following this, we can acknowledge how contemporary sport tourism trends vehicle complex forms of embodied subjectivity. Hence, I encourage a reading of the body in its ‘relational’ sense, emplaced (Howes, 2005; Pink, 2011) and in intra-action (Barad, 2007) with diverse human and non-human materialities. In addition, I propose the figuration ‘body-citycontinuum’ as an analytical tool that contribute to the purpose of broadening our understanding of corporality and to foster the creation of new economies of representation of the body in social sciences from a posthumanist standpoint.